2022
DOI: 10.1101/2022.11.30.517979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G2019S selective LRRK2 kinase inhibitor abrogates mitochondrial DNA damage

Abstract: Pathogenic mutations in LRRK2 cause Parkinson's disease (PD). The G2019S variant is the most common, which results in abnormally high kinase activity. Compounds that target LRRK2 kinase activity are currently being developed and tested in clinical trials. We recently found that G2019S LRRK2 causes mitochondrial DNA (mtDNA) damage and treatment with multiple classes of LRRK2 kinase inhibitors at concentrations associated with dephosphorylation of LRRK2 reversed mtDNA damage to healthy control levels. Because ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(122 reference statements)
1
5
0
Order By: Relevance
“…LRRK2 G2019S PD patient-derived LCLs also demonstrated increased mtDNA damage relative to age-matched controls (Fig. 2A), similar to previously published findings (15,20,37). mtDNA copy number was not different between idiopathic PD patientderived LCLs compared with age-matched healthy controls (Fig.…”
Section: Mtdna Damage Observed In Cells Derived From Patients With Id...supporting
confidence: 90%
See 3 more Smart Citations
“…LRRK2 G2019S PD patient-derived LCLs also demonstrated increased mtDNA damage relative to age-matched controls (Fig. 2A), similar to previously published findings (15,20,37). mtDNA copy number was not different between idiopathic PD patientderived LCLs compared with age-matched healthy controls (Fig.…”
Section: Mtdna Damage Observed In Cells Derived From Patients With Id...supporting
confidence: 90%
“…Many promising compounds or treatments targeting mitochondrial impairment in PD are in the pipeline (66,67). Yet, to date, a functional mitochondrial blood marker that could be used to establish a PD mitochondrial subtype that reflects this underlying pathophysiology has not been developed, thereby allowing a precision medicine-based approach to PD clinical trials, which may yield a higher chance of success (37,68). Our data provide evidence to support inclusion of mtDNA damage as a blood-based candidate marker for PD in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that lymphoblastoid cell lines and iPSC-derived neuronal cultures from LRRK2 p.G2019S mutation carriers have increased mtDNA damage 64 , 65 . When we genetically corrected the LRRK2 mutation or treated the cultures with a LRRK2 kinase inhibitor mtDNA damage was no longer detectable.…”
Section: Discussionmentioning
confidence: 97%